Comparison between the cultures of human induced pluripotent stem cells (hiPSCs) on feeder-and serum-free system (Matrigel matrix), MEF and HDF feeder cell lines - Ghasemi-Dehkordi, Payam (J Cell Commun Signal, 2015)
Human induced pluripotent stem cells (hiPSCs) are a type of pluripotent stem cells artificially derived from an adult somatic cell (typically human fibroblast) by forced expression of specific genes. In recent years, different feeders like inactivated mouse embryonic fibroblasts (MEFs), human dermal fibroblasts (HDFs), and feeder free system have commonly been used for supporting the culture of stem cells in undifferentiated state. In the present work, the culture of hiPSCs and their characterizations on BD Matrigel (feeder-and serum-free system), MEF and HDF feeders using cell culture methods and molecular techniques were evaluated and compared. The isolated HDFs from foreskin samples were reprogrammed to hiPSCs using gene delivery system. Then, the pluripotency ability of hiPSCs cultured on each layer was determined by teratoma formation and immunohistochemical staining. After EBs generation the expression level of three germ layers genes were evaluated by Q-real-time PCR. Also, the cytogenetic stability of hiPSCs cultured on each condition was analyzed by karyotyping and comet assay. Then, the presence of pluripotency antigens were confirmed by Immunocytochemistry (ICC) test and alkaline phosphatase staining. This study were showed culturing of hiPSCs on BD Matrigel, MEF and HDF feeders had normal morphology and could maintain in undifferentiated state for prolonged expansion. The hiPSCs cultured in each system had normal karyotype without any chromosomal abnormalities and the DNA lesions were not observed by comet assay. Moreover, up-regulation in three germ layers genes in cultured hiPSCs on each layer (same to ESCs) compare to normal HDFs were observed (p < 0.05). The findings of the present work were showed in stem cells culturing especially hiPSCs both MEF and HDF feeders as well as feeder free system like Matrigel are proper despite benefits and disadvantages. Although, MEFs is suitable for supporting of stem cell culturing but it can animal pathogens transferring and inducing immune response. Furthermore, HDFs have homologous source with hiPSCs and can be used as feeder instead of MEF but in therapeutic approaches the cells contamination is a problem. So, this study were suggested feeder free culturing of hiPSCs on Matrigel in supplemented media (without using MEF conditioned medium) resolves these problems and could prepare easy applications of hiPSCs in therapeutic approaches of regenerative medicine such as stem-cell therapy and somatic cell nuclear in further researches.